Given a sequence $\{x_n\}, \ n\in\Bbb N$: $$ x_n = \frac{(2n)!!}{(2n+1)!!} $$ Show that $x_n$ converges.

I'm wondering why I'm getting a seemingly wrong result (assuming the problem statement asks to prove convergence): $$ \begin{align} x_n &= \frac{(2n)!!}{(2n+1)!!} \\ &= \frac{2\cdot 4\cdot 6\cdots (2n-2)\cdot(2n)}{3\cdot 5\cdot 7\cdots (2n-1)\cdot(2n+1) } \\ &= \frac{2\cdot 4\cdot 6\cdots (2n-2)\cdot(2n)}{3\cdot 5\cdot 7\cdots (2n-1)\cdot(2n+1)} \cdot \frac{2(n)!}{2(n)!} \\ &= \frac{4^n (n!)^2}{(2n+1)!} \\ &= \frac{4^n (n!)^2}{(2n+1)\cdot (2n)!} \\ &=\frac{4^n}{2n+1}\cdot \frac{(n!)^2}{(2n)!} \end{align} $$

By Binomial coefficients: $$ {2n\choose n} = \frac{(2n)!}{n!(2n-n)!} = \frac{(2n)!}{(n!)^2} $$

Thus: $$ x_n = \frac{4^n}{2n+1}\cdot \frac{1}{{2n \choose n}} $$

Doesn't $\frac{4^n}{2n+1}$ grow faster than $\frac{1}{2n\choose n}$ is declining? Shouldn't $x_n$ diverge in that case?

  • $\begingroup$ I don't see how $$\frac{2\cdot 4\cdot 6\cdots (2n-1)\cdot(2n)}{3\cdot 5\cdot 7\cdots (2n-1)\cdot(2n+1)} \cdot \frac{(2n)!}{(2n)!} = \\= \frac{4^n (n!)^2}{(2n+1)!} $$ would be true. $\endgroup$ – 5xum Jan 3 at 13:05
  • $\begingroup$ The asymptotic behavior of $\binom {2n} n$ could be determined by Stirling approximation. It may not be slow as you think. $\endgroup$ – xbh Jan 3 at 13:05
  • $\begingroup$ @5xum I made a mistake in the nominator. $\endgroup$ – roman Jan 3 at 13:08
  • $\begingroup$ @5xum, there is a mistake in the notation, it should be 2(n!) instead of (2n)! to make this result true. You can then compute this using Stirling. $\endgroup$ – S. Franssen Jan 3 at 13:12

You have

$$0\leq x_{n+1} = x_n \cdot \frac{2n+2}{2n+3} \leq x_n$$ thus, your sequence is monotone decreasing and bounded from below and therefore convergent.


Using the Stirling approximation for factorials we can observe the following: $n! \sim \sqrt{2 \pi n} \left( \frac{n}{e} \right)^n$. This means that, while being a bit sloppy with the $\sim$

$ \begin{align*} x_n &= \frac{(2n)!!}{(2n+1)!!} \\ &= \frac{4^n (n!)^2}{(2n+1) (2n)!}\\ & \sim \frac{4^n 2 \pi n \left( \frac{n}{e} \right)^{2n}}{ (2n+1) 2\sqrt{\pi n} \left(\frac{2n}{e} \right)^{2n}}\\ &= \frac{\sqrt{\pi n}}{2 n + 1} \rightarrow 0 \end{align*} $

So $x_n \rightarrow 0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.